(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The WORLD TRADE ORGANIZATION (WTO) concluded negotiations on financial services in the context of the General Agreement on Trade in Services (GATS) in December 1997. These services include banking, insurance and other financial services, which have become subject to multilateral trade rules. i.e., any country acceding to the WTO is obliged to open such a sector of strategic importance. Sudan, a developing economy, practicing Islamic Banking System and has an observer status at the WTO. The economic literature consistently pointed to the crucial role of financial development in a country’s economic growth. It is now almost axiomatic to state that a well performing financial sector promotes economic growth through a multitude of channels, well known among which is the enhancement of the rate of accumulation and efficiency of capital. By 1985, Islamic financial products offered by more than 50 conventional banks around the globe. By 2010, Islamic banking and finance became one of the world’s fastest-growing economic sectors that comprise more than 400 institutions with assets under management in excess of one trillion ( 1,000 billion), (Dubai Islamic Bank http://www.dib.ae). A study by Eltayeb (2005, pp. 1-46) summarizes the situation for countries adopting Islamic banking practices. The aim of his study was to examine the effectiveness of the Islamic Banks in facing international competition in the context of financial liberalization of the GATS. The study concluded that, the GATS imposed a number of challenges on the Islamic Banks and that these challenges should be faced through adopting an efficient strategy based on offering comprehensive banking services that cope with technological innovations and development and meet international standards while maintaining strong ties with foreign banks particularly those with Islamic windows. In addition, the study recommends the insertion of Islamic Banking Services in the obligations’ schedules to gain the maximum benefits from the facilities offered by the GATS agreement. The aim of this paper is to overview some literature on the GATS, as well as, the Islamic Banking system in Sudan and provide some recommendations to assist this country in its anticipated accession to the WTO. The paper concluded with some recommendations out of which are: - It may be useful for Sudan to solve the problems that crippled the production in the agricultural sector, to encourage commercial banks to extend finance to it. The Salam mode of finance should be enhanced. - The Sudanese commercial banks are recommended to continue increasing the level of their investments in modern banking services technology. - Commercial banks are also recommended to follow the Central Bank of Sudan instructions for merging, to improve their abilities to compete on the international level. - Commercial banks should diversify their provided banking services, as well as innovate new banking services to meet the increasing demands of their clients. - The manpower in these commercial banks should be given more attention through training and skills upgrading, that will enable them to use the modern technology more efficiently.